2012
DOI: 10.4103/0255-0857.99504
|View full text |Cite
|
Sign up to set email alerts
|

Case of Phthiriasis palpebrarum with blepheroconjunctivitis

Abstract: A 70-year-old woman came to ophthalmology outpatient department with complaints of repeated episodes of itching, redness and watering in both eyes of 3 months duration. She was treated with antibiotics elsewhere but had no improvement. Slit lamp examination showed lice and nits anchored to the eyelashes. Light microscopic examination of the matted eye lashes and crusts further helped in identification of the ectoparasites as Phthirus pubis (Pubic louse or Crab louse) with typical morphology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
17
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 10 publications
1
17
0
Order By: Relevance
“…We also found lice in the scalp hairs of this girl. Kiran et al [5] also recently reported a 70-year-old woman who complained of repeated episodes of itching, and redness and watering in both eyes for 3 months with no any improvement after treatment with antibiotics. During the slit lamp examination, the lice and nits anchored to the eyelashes were finally found.…”
Section: Discussionmentioning
confidence: 96%
“…We also found lice in the scalp hairs of this girl. Kiran et al [5] also recently reported a 70-year-old woman who complained of repeated episodes of itching, and redness and watering in both eyes for 3 months with no any improvement after treatment with antibiotics. During the slit lamp examination, the lice and nits anchored to the eyelashes were finally found.…”
Section: Discussionmentioning
confidence: 96%
“…In children, eyelashes are the most common site of the infestation [ 10 , 14 ] and phthiriasis palpebrarum may be a sign of sexual abuse, and the possibility of abuse should be investigated. Transmission by bed linens and infested clothing is less likely and doubted by some [ 7 , 10 , 14 , 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Ocular signs and symptoms include bilateral ocular itching, irritation, observation of lice and nits, erythematous lesions (from louse bites), reddish brown deposits on the lashes, secondary blepharitis, follicular conjunctivitis and marginal keratitis (Pinckney et al, 2008). Intense pruritus caused by the saliva of the louse lead to scratching, inflammation, eczema and superadded bacterial infection (Kiran et al, 2012). Although phthiriasis may be acquired via close contact with infested individuals or contaminated clothing, towels and bedding, the parasites are typically sexuallytransmitted.…”
Section: Phthiriasis Palpebrarum: a Common Parasite With An Uncommon mentioning
confidence: 99%